Genetic Risk for Psychiatric Disorders and Telomere Length - Palmos, Alish B.; Breen, Gerome; Goodwin, Laura; Frissa, Souci; Hatch, Stephani L.; Hotopf, Matthew; Thuret, Sandrine; Lewis, Cathryn M.; Powell, Timothy R. (Frontiers in Genetics, 2018)
Background: Previous studies have revealed associations between psychiatric disorder diagnosis and shorter telomere length. Here, we attempt to discern whether genetic risk for psychiatric disease, or use of pharmacological treatments (i.e. antidepressants), predict shorter telomere length and risk for ageing-related disease in a UK population sample. Methods: DNA samples from blood were available from 351 participants who were recruited as part of the South East London Community Health (SELCoH) Study, and for which whole-genome genotype data was available. Leukocyte telomere length was characterized using quantitative polymerase chain reactions. Individualized polygenic risk scores for major depressive disorder (MDD), bipolar disorder (BD) and schizophrenia (SCZ) were calculated using Psychiatric Genomics Consortium summary statistics. We subsequently performed linear models, to discern the impact polygenic risk for psychiatric disorders (an aetiological risk factor) and antidepressant use (common pharmacological treatment) have on telomere length, whilst accounting for other lifestyle/health factors (e.g. BMI, smoking). Results: There were no significant associations between polygenic risk for any of the psychiatric disorders tested and telomere length (p>0.05). Antidepressant use was significantly associated with shorter telomere length and this was independent from a depression diagnosis or current depression severity (p≤0.01). Antidepressant use was also associated with a significantly higher risk of ageing-related disease, which was independent from depression diagnosis (p≤0.05). Conclusions: Genetic risk for psychiatric disease is not associated with shorter telomere length. Further studies are now needed to prospectively characterise if antidepressant use increases risk for ageing related disease and telomere shortening, or whether people who age faster and have ageing-related diseases are just more likely to be prescribed antidepressants.